Synthesis of Nanosilica from Padas Stone to Reduce The Total Organic Carbon of Palm Oil Waste - Shofiyani, Anis; Chitra, Fara; Rahmalia, Winda; Rudiyansyah, R.; Alimuddin, Andi Hairil (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2019)
Padas stone is one of the natural mineral containing 67.5% of SiO2 compounds. In this research, synthesis of nanosilica was carried out by sol-gel method asistanced by 2.45 GHz microwave radiations with low (10%), medium (50%) and high (100%) power at 30 and 60 minutes of contact times. It was analyzed by XRD, BET, FTIR spectrophotometry and SEM. The synthesized silica was then used as absorbent for total organic carbon (TOC) of palm oil waste. The results show that the synthesized silica was a mixture of cristobalite and quartz type minerals according to ICDD No. 00-003-0271 and 01-083-287. The surface area and silicon dioxide contains are 12.174 m2/g and 76.325% for silica without microwave assistance (SiO2-TPMW); 12.796 m2/gand 86.385% for silica with 30 minutes on 10% microwave assistance(SiO2 -MW 10A); 12.735 m2/gand 86.254% for silica with 60 minutes on 10% microwave assistance (MW 10B); 13,659 m2/gand 87.211% for MW 50A; 13,583 m2/g and 86.684% for MW 50B;7.883 m2/gand 57.527% for MW 100A; also 8.752 m2/g and 37.725% for MW 100B, respectively. The use of silica as an absorbent of TOC shows the effectiveness of 62.89% (TPMW); 63.68% (MW 10A); 62.96% (MW 10B); 65.25% (MW 50A); 64.61% (MW 50B); 62.37% (MW 100A) and 61.18% (MW 100B) from the initial TOC of 1520 mg/L. Keywords: synthesis, nanosilica, padas stone, total organic carbon, oil waste.